2019
DOI: 10.31014/aior.1993.02.02.76
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Increase Efficacy and Interdependence in Group Work

Abstract: The Education Quarterly Reviews is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license. The Asian Institute of Research Education Quarterly Reviews is a peer-reviewed International Journal. The journal covers scholarly articles in the fields of education, linguistics, literature, educational theory, research, and methodologies, curriculum, elementary and secondary education, higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Group work is a major approach of the (SMC) framework. Previous research reported a positive impact on students' learning, understanding, and motivation (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), and a positive influence on their self-efficacy (Wyatt, 2010;Mitcham et al, 2012;Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019), especially when students learn how to work and think together as a group (Wegerif et al, 2017). Chambers and Timlin (2013) provided some detail about…”
Section: Smc: the Conceptual Framework For The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Group work is a major approach of the (SMC) framework. Previous research reported a positive impact on students' learning, understanding, and motivation (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), and a positive influence on their self-efficacy (Wyatt, 2010;Mitcham et al, 2012;Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019), especially when students learn how to work and think together as a group (Wegerif et al, 2017). Chambers and Timlin (2013) provided some detail about…”
Section: Smc: the Conceptual Framework For The Studymentioning
confidence: 99%
“…This has also been confirmed by this study, as the following interview extract shows. (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), but also improved their self-efficacy as well (Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019). Group work was involved while playing the puzzle sheets, answering the revision notes, and while using different teacher's teaching methodologies.…”
Section: What Features Within the Framework Promoted Improved Students' Self-efficacy Andmentioning
confidence: 99%
“…This requirement is based on the interaction and interdependence of education and scientific research focuses to ensure awareness of modern knowledge. Other authors argued that sciencebased education is the most important thing in modern education (Chiriac et al 2019;Physical Education Teacher in Middle Schools: Requirements … International Journal of Instruction, July 2024• Vol.17, No.3 Scager et al 2016. So, science-based education is important in all stages and types of education including middle schools.…”
Section: Physical Education Teacher In Middle Schools: Requirements …mentioning
confidence: 99%
“…Более 50% детей контрольной группы осталась безучастной к групповой деятельности. Автором [2], [3], [4], [5], [6], [7].…”
Section: формирование групповой самоэффективности в условиях осуществления совместной деятельности у детей дошкольного возрастаunclassified
“…совместная непринужденная партнерская деятельность взрослого с детьми, 2. свободная самостоятельная деятельность самих детей, выбор которой обеспечивается взрослым-воспитателем 7 .…”
Section: формирование групповой самоэффективности в условиях осуществления совместной деятельности у детей дошкольного возрастаunclassified